INDONESIA'S DEFENSE OF SEBATIK ISLAND IN A BORDER DISPUTE BASED ON THE PRINCIPLE OF UTI POSSIDETIS - Rahmadhani, Novia; Anh, Nguyen Thuy; Suryaningtias, Allysa Maharani; Azarya, Ryan Phillip; Utama, Meria; Nurliyantika, Rizka (Sriwijaya Crimen and Legal Studies, 2024)
Indonesia is the largest archipelagic country on the Asian continent, with more than 17,000 islands. The government has yet to identify many small and outermost islands in detail. Identifying these outer islands further emphasizes the sovereignty of the Republic of Indonesia regarding the location of the country's borders. Border areas are an essential aspect because they are a marker of a country's jurisdiction. Border areas are an arena for interactions between global and local communities that occur every day. Indonesia has several disputes with neighboring countries about the outer islands directly adjacent to it. Sebatik Island is one of the disputed islands. Meanwhile, Indonesia obtained its territory according to colonial jurisdiction. Sebatik Island which was obtained based on the Uti Possidetis principle. The research method used is normative juridical, examining library materials through norms, rules, legal principles, and doctrine. Among them are the Technical Aspects of the United Nations Convention on the Law of the Sea (TALOS) and the United Nations Convention on the Law of the Sea (UNCLOS). This paper examines Indonesia's potential to defend Sebatik Island using the Uti Possidetis principle. This principle holds that the territories of former colonies should be recognized as independent states with the same borders they had before colonization. By invoking this principle, Indonesia sought to assert its rightful claim to Sebatik Island and protect its sovereignty. Many countries have recognized this legal precedent, and have been used to resolve other border disputes worldwide.